Entre le journal intime et le monologue corporel — Splendid Hôtel de Marie Redonnet - Kotowska, Katarzyna (Verbum – Analecta Neolatina, 2009)
The narrative structure in Marie Redonnet’s novel Splendid Hôtel (Splendid Hotel) is ambiguous. It has the characteristic features of the literary genre, diary (journal intime). In the novel, the Narrator - a woman with indefinite name and age - reports all prominent measures she has undertaken while she was running a hotel, a property she had inherited from her grandmother. She tries to cope with different kinds of pests (flies, mosquitoes, rats, bedbugs, spiders, termites), workers (carpenters, cabinetmakers, thatchers, plumbers) and their bills, and guests (prospectors, geologists, team foremen, engineers). She also copes with two spoiled and irritating sisters: sickly Ada and a would-be actress - Adel. Redonnet makes a skillful use of metaphoric possibilities. Splendid Hôtel remains a female body, and the body seems to be the actual author of monologue. That is why the monologue can be called ’corporeal’.